Heterochromatin variation in chromosomes of Anopheles (Nyssorhynchus) darlingi Root and A. (N.) nuneztovari Gabaldon (Diptera: Culicidae) - Rafael, Míriam Silva (2000)
C-banding was used to study the variations in heterochromatic block markings in chromosomes of Anopheles darlingi and A. nuneztovari from Manaus, State of Amazonas, and Macapa, State of Amapa, Brazil. Both species had two differently shaped X chromosomes and a Y chromosome that was entirely heterochromatic. The X1 chromosome of A. darlingi had markings that extended 1/3 of the total length whereas in the X2 chromosome the markings were located around the centromeric region. The markings on autosomal chromosomes were concentrated in the centromeric region in both species, with a heterochromatic block in one arm of chromosome II of A. darlingi. A. nuneztovari had three heterochromatic blocks in chromosome X1 (longer) and two blocks in X2 (shorter). X2X2 females were not detected in either species. The X1 and X2 chromosomes of males were found in A. darlingi, whereas in A. nuneztovari only the X1 chromosome was detected. Only intraspecific variation was found in heterochromatic block markings in the sex chromosomes and autosomes in the two populations of both species at each location.